Tertiary lymphoid structures and B lymphocytes: a promising therapeutic strategy to fight cancer - Esparcia-Pinedo, Laura; Romero-Laorden, Nuria; Alfranca, Arantzazu (Frontiers in Immunology, 2023)
Tertiary lymphoid structures (TLSs) are clusters of lymphoid cells with an organization that resembles that of secondary lymphoid organs. Both structures share common developmental characteristics, although TLSs usually appear in chronically inflamed non-lymphoid tissues, such as tumors. TLSs contain diverse types of immune cells, with varying degrees of spatial organization that represent different stages of maturation. These structures support both humoral and cellular immune responses, thus the correlation between the existence of TLS and clinical outcomes in cancer patients has been extensively studied. The finding that TLSs are associated with better prognosis in some types of cancer has led to the design of therapeutic strategies based on promoting the formation of these structures. Agents such as chemokines, cytokines, antibodies and cancer vaccines have been used in combination with traditional antitumor treatments to enhance TLS generation, with good results. The induction of TLS formation therefore represents a novel and promising avenue for the treatment of a number of tumor types.